2017
DOI: 10.1080/01443615.2017.1329284
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of labour in term premature rupture of membranes; oxytocin versus sublingual misoprostol; a randomised clinical trial

Abstract: Premature rupture of the membranes (PROM) occurs in about 8-10% of pregnancies and its most important complication is chorioamnionitis, so labour induction has an important role in this situation. This study was performed to compare oxytocin and sublingual Misoprostol for labour induction in PROM cases with term pregnancy. A total of 270 pregnant women who had spontaneous rupture of membrane and unripe cervix were enrolled. The first group underwent Oxytocin infusion according to low-dose standard protocol and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 21 publications
2
23
1
1
Order By: Relevance
“…One randomized study found that induction with 25 mcg of sublingual (equivalent to buccal) misoprostol shortens the duration of active labor and the second stage with similar time intervals from induction to the second stage compared with a low-dose oxytocin protocol. 10 This study did not evaluate overall induction-to-delivery times, which makes it difficult to directly compare our results. However, the study also excluded any patients who received oxytocin after sublingual misoprostol and therefore may represent a different patient population from our study, which evaluated only the initial induction agent after PROM.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…One randomized study found that induction with 25 mcg of sublingual (equivalent to buccal) misoprostol shortens the duration of active labor and the second stage with similar time intervals from induction to the second stage compared with a low-dose oxytocin protocol. 10 This study did not evaluate overall induction-to-delivery times, which makes it difficult to directly compare our results. However, the study also excluded any patients who received oxytocin after sublingual misoprostol and therefore may represent a different patient population from our study, which evaluated only the initial induction agent after PROM.…”
Section: Resultsmentioning
confidence: 98%
“…8,9 However, limited data are available in the setting of induction after PROM, with a single study suggesting sublingual administration may be more effective than oxytocin. 10 The primary purpose of our study was to compare admission-to-delivery times in nulliparous patients with PROM and unfavorable cervices or unknown cervical dilation when induced with buccal misoprostol versus intravenous oxytocin. Given prior data that suggest oxytocin is equivalent or superior to vaginal prostaglandins and the similar bioavailability between buccal and vaginal misoprostol, we hypothesized that oxytocin would also be associated with faster admission-to-delivery times than buccal misoprostol.…”
mentioning
confidence: 99%
“…10 Vaginal or oral misoprostol could improve Bishop score in this patients. 11 In this sense, oral misoprostol seems to have a lower rate of caesarean section. 12 Moreover time to delivery is lower with oral misoprostol.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini diperkuat oleh hasil beberapa penelitian lain yang menemukan hal serupa, bahwa mayoritas penggunaan off-label Misoprostol adalah untuk menginduksi persalinan [26,27]. Hal tersebut dikarenakan Misoprostol memberikan efek uterotonik dan pelembutan pada rahim [28].…”
Section: Kategori Penggunaan Obat Off-label Misoprostolunclassified